Analisis Pengaruh Kualitas Pelayanan, Harapan Pelanggan dan Kepercayaan terhadap Kepuasan Pelanggan PT. PLN (Persero) - Eva Puspita Damayanti; Aswin Naldi Sahim; Irawan R. D Budianto (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study examines PT. PLN (Persero) customer satisfaction concerns that are still impacted by inconsistent service quality, unfulfilled consumer expectations, and varying degrees of trust. The purpose of the study is to examine how customer happiness is impacted by service quality, customer expectations, and trust, both separately and collectively. Descriptive and associative design were used in a quantitative approach. 10,378 PT. PLN (Persero) clients made up the population, and the Slovin algorithm was used to select a sample of 100 responses. Structured questionnaires and observations were used to gather the data, which were then subjected to multiple linear regression analysis using SPSS version 24 with the use of traditional assumption testing. The findings show that customer happiness is significantly impacted by service quality, customer expectations, and trust. Simultaneously, these three variables contribute meaningfully to explaining variations in customer satisfaction, although other factors beyond the research model also play a role. The findings highlight the importance of improving service consistency, aligning services with customer expectations, and strengthening customer trust to enhance overall satisfaction. This study provides empirical evidence that can support managerial decision-making in improving service performance at PT. PLN (Persero).